Differences in visual-spatial working memory and driving behavior between morning-type and evening-type drivers. (March 2020) - Ge, Yan; Sheng, Biying; Qu, Weina; Xiong, Yuexing; Sun, Xianghong; Zhang, Kan
Highlights: The evening-type drivers showed different direction in self-reported driving behavior and simulated driving behavior. The evening-type drivers self-reported more dangerous driving behaviors but had better lateral control on the simulated driving task than morning-type drivers. The evening-type drivers had greater accuracy in the visual-spatial working memory task than morning-type drivers. The ability of visual-spatial working memory could predicted the simulated driving behavior. Abstract: Circadian rhythms are changes in life activities over a cycle of approximately 24 hours. Studies on chronotypes have found that there are significant differences in physiology, personality, cognitive ability and driving behavior between morning-type and evening-type people. The purpose of this study is to explore the relationship between visual-spatial working memory and driving behavior between morning-type and evening-type drivers in China. A total of 42 Chinese drivers were selected to participate in this study according to their score on the Morningness-Eveningness Questionnaire, including 22 morning-type drivers and 20 evening-type drivers. During the experiment, the participants completed one cognitive task (visual-spatial working memory), two simulated driving tasks (car-following task and pedestrian-crossing task), and the Dula Dangerous Driving Index (DDDI). The results showed that evening-type drivers self-reported more dangerous driving behaviors but had better lateral control on the simulated driving task than morning-type drivers. In addition, evening-type drivers had greater accuracy when performing the visual-spatial working memory task. Moreover, the accuracy on the visual-spatial working memory task positively predicted the percentage of time over the speed limit by 10 mph (POS10) and negatively correlated with the reaction time measure (time to meet pedestrians) in the pedestrian-crossing task. The relationships among chronotype, cognitive ability and driving behavior are also discussed. Understanding the underlying mechanisms could help explain why evening-type drivers perform dangerous driving behaviors more often.